Pengaruh Model Pembelajaran KWL (Know, Want To Know, Learned) Terhadap Keaktifan, Minat, dan Motivasi Belajar IPAS Siswa - Nurhayati Nurhayati; Hartini Hartini; Andi Mulyadi Radjab (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study investigated the effect of the KWL (Know, Want to Know, Learned) learning model on students' learning activeness, interest, and motivation in IPAS learning at UPT SDN Padang No. 3 Kepulauan Selayar. A quasi-experimental non-equivalent control group design was used with 30 fifth-grade students divided into an experimental group and a control group. Data were collected through observation sheets, questionnaires, pretest-posttest documentation, and analyzed using prerequisite tests and MANOVA. The experimental group showed higher mean scores than the control group in activeness (26.47 vs. 24.73), learning interest (106.40 vs. 86.80), motivation (108.93 vs. 89.20), and posttest achievement (86.73 vs. 75.87). MANOVA indicated a significant simultaneous effect of KWL on the three dependent variables (Wilks' Lambda = 0.064; F = 127.497; p < 0.001). Follow-up tests confirmed significant effects on activeness (F = 9.188; p = 0.005), interest (F = 216.865; p < 0.001), and motivation (F = 153.905; p < 0.001). KWL effectively improves students' active and affective learning engagement in IPAS